Fixed-Time Connectivity Preserving Tracking Consensus of Multiagent Systems with Disturbances - Fenglan Sun; Peiyong Liu; Jürgen Kurths; Wei Zhu (Complexity)
This text studies the fixed-time tracking consensus for nonlinear multiagent systems with disturbances. To make the fixed-time tracking consensus, the distributed control protocol based on the integral sliding mode control is proposed; meanwhile, the adjacent followers can be maintained in a limited sensing range. By using the nonsmooth analysis method, sufficient conditions for the fixed-time consensus together with the upper and lower bounds of convergence time are obtained. An example is given to illustrate the potential correctness of the main results.